AKTIVITAS ANTIKANKER SENYAWA PTEROKARPAN DARI Erythrina fusca L. - Anggreini, Novi (Jurnal Farmasi Medica/Pharmacy Medical Journal (PMJ), 2018)
AKTIVITAS ANTIKANKER SENYAWA PTEROKARPAN DARI Erythrina fusca L. Novi Anggreini1), Ratih Dewi Saputri1), Tjitjik Srie Tjahjandarie1), Mulyadi Tanjung1*)1)Natural Products Chemistry Research Group, Organic Chemistry Division,Department of Chemistry, Faculty of Science and Technology, Universitas Airlangga, Surabaya 60115, Indonesiamulyadi-t@fst.unair.ac.id  ABSTRACT Two pterocarpans  namely as sandwicensin (1)  dan phaseollin (2) were isolated from  the stem bark of. Erythrina fusca L. Their structures were determined  based on spectroscopic data such as UV, IR, MS, 1D and 2D NMR. Compounds 1–2 were evaluated for their anticancer against murin leukemia P-388 cells showing their IC50 were 1.20 and 1.05 µg/ml, respectively and very high activity. Keywords : Erythrina fusca L., sandwicensin, phaseollin, anticancer  ABSTRAK Dua senyawa pterokarpan yakni sandwisensin (1)  dan paseollin (2) telah diisolasi dari kulit batang Erythrina fusca L. Struktur senyawa pterokarpan ditetapkan berdasarkan analisis spektroskopi UV, IR, MS, 1D dan 2D NMR. Uji aktivitas antikanker senyawa 1–2 terhadap sel murin leukemia P-388 memperlihatkan IC50 1,20 dan 1,05 µg/ml yang dikategorikan sangat aktif. Kata kunci : Erythrina fusca L., sandwisensin, paesolin, antikanker